Quantification of training and match load in elite youth soccer players: a full-season study - Nobari, H.; Barjaste, A.; Haghighi, H.; Clemente, F. M.; Carlos-Vivas, J.; Perez-Gomez, J. (The Journal of Sports Medicine and Physical Fitness, 2022)
BACKGROUND: The present study aimed to quantify training and match load in elite young soccer players over the course of an entire season. METHODS: Using a longitudinal design, session-rate of perceived exertion (s-RPE) and its metrics (weekly acute workload [wAW], acute to chronic workload ratio [wACWR], training monotony and training strain) were examined in twenty-one elite young soccer players (mean±standard deviation; age: 16.1±0.2 years; height: 176.8±5.6 cm; body mass: 67.3±5.7 kg; BMI: 21.5±1.4 kg/m2; VO2max: 47.6±3.8 mL/kg/min) during the whole season containing 4 meso-cycles: preseason (Pre-S), early-season (Ear-S), mid-season (Mid-S), and end-season (End-S). RESULTS: Repeated-measures analysis of variance examined variations in s-RPE load data across the 4 meso-cycles and 1-week of microcycle. Analyzing data revealed the End-S had a significant greater wAW compared to Early-S (P=0.002, g=0.96) and Mid-S (P<0.001, g=1.09). However, no differences between in-season periods were observed in wACWR (P=0.524). The within-week variations revealed significant lower wAW in prematch a day (MD-1) (P<0.001), 1 day after match (MD+1) (P<0.001) and 2 days after match (MD+2) (P<0.001) compared to match day (MD) for overall team analysis. Additionally, analyses by playing position showed that fullbacks have a significant lower AW in MD+2 compared to MD (P<0.029). CONCLUSIONS: The periodization of training load indicated variations across the whole season in young elite players. The weekly microcycle perceived load could be identified as follows; there are higher training loads on MD-3 and MD-2 which was similar to intensities experienced by players throughout the match play and, furthermore, lower overall WL on the MD+1 and MD+2 in order to ensure the optimal recovery of the players.